The detection of tyrosinase-specific mRNA in bone marrow is not more sensitive than in blood for the demonstration of micrometastatic melanoma - Waldmann, Volker; Deichmann, Martin; Bock, Michael; Jäckel, Andreas; Näher, Helmut (British journal of dermatology, 1999)
Recent reports suggest that as a marker of progression of malignant melanoma, the detection of tyrosinase mRNA in blood is of limited value. In the present study, we investigated whether the detection of tyrosinase mRNA by reverse transcription-polymerase chain reaction (RT-PCR) in bone marrow samples might be a more useful method for the detection of micrometastatic melanoma. The presence of tyrosinase mRNA was analysed in blood and in bone marrow samples from 20 melanoma patients with widespread clinical metastases. Of these 20 patients, 12 were negative for tyrosinase mRNA in both blood and bone marrow. The remaining eight patients had tyrosinase mRNA in either blood or bone marrow: six in bone marrow and blood, one in bone marrow but not blood, and one in blood but not bone marrow. The sensitivity of tyrosinase mRNA detection by RT-PCR in bone marrow samples apparently does not exceed that in blood samples from metastatic melanoma patients. This seems to be independent of prior chemotherapy or immunotherapy. In contrast to different solid tumours, in melanoma, bone marrow seems not to be a significant reservoir for micrometastatic tumour cells.